Transformation of Village Library to Social Inclusion-Based Library for Community Entrepreneurship (Case Study of Rambung Sialang Hulu Village Library, Sergei District, Deli Serdang Regency) - Doni Sabdan Tanjung; Nursapiah Harahap (PT Mattawang Mediatama Solution, 2023)
This study aims to identify and examine the efforts and active role of the Rambung Sialang village library and its transformation and contribution to the development of entrepreneurship in the Rambung Sialang Hulu village community. The research method used is a qualitative research method with a phenomenological approach. The data collection technique used is the observation technique. The results of the research show that the village library can be used as a learning tool for the community as well as a means to encourage the welfare of the village community. The Rambung Sialang Hulu village library plays an active role in improving the existing human resources in the village, this can be seen from the programs being implemented which are programs that can increase creativity so as to create a good quality of life for the community. Efforts made by the village library are by transforming the library based on social inclusion. The contribution of the Rambung Sialang village library in addition to developing human resources also provides solutions to develop community entrepreneurship. The Rambung Sialang Hulu village library collaborates with village communities to develop villages by developing community competencies and by utilizing existing facilities and programs. The Rambung Sialang Hulu village library often provides promotional and marketing media for entrepreneurial products. The Rambung Sialang Hulu village library will also look for more marketing media that can be used to improve the welfare of the people of Rambung Sialang Hulu village.